1993
DOI: 10.1007/bf01067984
|View full text |Cite
|
Sign up to set email alerts
|

A genetic, physiological, and biochemical investigation of audiogenic seizures in rats

Abstract: Two kinds of audiogenic seizures are characteristic of the KM rat strain, selected by Krushinsky and Molodkina in Moscow in the 1940s. This strain is now approximately 100% sound sensitive. Diallel crosses have demonstrated the polygenic nature of this behavior, with most alleles for seizures being recessive. Myoclonic seizures which develop after several sound exposures are a special form of kindling, involving the limbic system. Selection for low and high rates of myoclonic seizures was successful. Several u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…The heritability of audiogenic seizure in rats was no less simple issue. In KM rats the diallelic cross showed that AE heritability is polygenic with additive effects, and alleles determining the resistance to sound induced seizures were dominant (Romanova et al, 1993). The data on the genetic experiments in other AE rat strains are the following.…”
Section: Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heritability of audiogenic seizure in rats was no less simple issue. In KM rats the diallelic cross showed that AE heritability is polygenic with additive effects, and alleles determining the resistance to sound induced seizures were dominant (Romanova et al, 1993). The data on the genetic experiments in other AE rat strains are the following.…”
Section: Geneticsmentioning
confidence: 99%
“…This selection was successful and the maximum selection effect in both new substrains was achieved in 4-5 generations. This made it possible to suggest that the predisposition for audiogenic kindling development is the oligogenic trait (Romanova et al, 1993). In mouse no data exist about the possibility to induce the audiogenic kindling.…”
Section: Myoclonic Seizures Induced By Repetitive Audiogenic Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In KM rats audiogenic seizures can be evoked by acoustic stimulation [10]. Repetition of the seizures results in their prolongation, which is a reliable marker of the epileptogenic process called audiogenic kindling [11].…”
Section: Introductionmentioning
confidence: 99%
“…Repeated administration of the eCB agonist WIN55,212-2 (WIN) has been shown to retard electrical kindling [9] but the chronic treatment protocol complicates dissecting acute anticonvulsive and long-term anti-epileptogenic drug effects. The present study was designed to examine effects of WIN in a single-injection experiment in Krushinsky-Molodkina (KM) rats with genetic audiogenic epilepsy [10].…”
Section: Introductionmentioning
confidence: 99%